Urgency of Evaluation of Stunting Handling Programs and Activities - Sujatmiko, Edy (Jurnal Keperawatan Profesional (KEPO), 2025)
Stunting remains a serious public health issue in Indonesia, including in Jepara Regency, due to its detrimental effects on children’s physical growth and cognitive development, threatening future human resource quality. Addressing stunting in Jepara is crucial given its high prevalence and long-term consequences. This study aimed to evaluate the effectiveness of stunting prevention programs in Jepara and to identify weaknesses and opportunities for improvement. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and document analysis. Content analysis was applied to assess program effectiveness, identify obstacles, and formulate strategic recommendations. Interventions such as supplementary feeding (PMT) and integrated activities at village and sub-district levels showed mixed results. Among 41 children who received PMT for 90 days, only 2 successfully overcame stunting. The limited success was attributed to poor cross-sector coordination, suboptimal resource allocation, and low community participation. To enhance program effectiveness, a prevention-based approach is needed, including strengthening governance, developing technology-based data systems, and increasing community involvement. This study provides strategic recommendations to support the reduction of stunting prevalence in Jepara and contributes to achieving the national stunting reduction targets.